Deal or no deal - What's at stake for ACP countries with a hard Brexit? - Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2019)
A few weeks before the Brexit date of 31 October 2019, the big questions remain unanswered: Will Britain withdraw from the European Union? And if so, with or without a deal? These decisions not only affect the European Union and the United Kingdom itself, they also have consequences for the 79 countries of the ACP group, which have many links with both partners. Above all, a 'hard brexit' would create uncertainty for ACP countries and jeopardise their development opportunities. In the event of a disorderly Brexit, however, these risks for the ACP countries arise not so much from international trade as from possible changes in development policy.
Keywords: 330